PSYCHOMOTOR SKILLS AS A PART OF POLYTECHNICAL EDUCATION - HONZIKOVA, Jarmila (Trends in education, 2015)
The article introduces the notion of polytechnical education. It describes the development of psychomotor skills since the early age up until the age of elementary school. This kind of development is demonstrated via two tasks - cutting and folding the paper. These two tasks are part of a testing battery which helps to find out the level of psychomotor skill.
Keywords: psychomotor skills; polytechnical education; research.